2015
DOI: 10.1158/2159-8290.cd-15-0399
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity Underlies the Emergence of EGFRT790 Wild-Type Clones Following Treatment of T790M-Positive Cancers with a Third-Generation EGFR Inhibitor

Abstract: Rociletinib is a third-generation EGFR inhibitor active in lung cancers with T790M, the gatekeeper mutation underlying most first-generation EGFR drug resistance. We biopsied patients at rociletinib progression to explore resistance mechanisms. Among 12 patients with T790M-positive cancers at rociletinib initiation, six had T790 wild-type rociletinib-resistant biopsies. Two T790 wild-type cancers underwent small cell lung cancer transformation; three T790M-positive cancers acquired EGFR amplification. We docum… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
371
1
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 432 publications
(397 citation statements)
references
References 29 publications
19
371
1
6
Order By: Relevance
“…These results suggest that mutation clonality, as it exists in tumor tissue, can be estimated from properly normalized relative cfDNA VAFs, as has been previously hypothesized (28). High accuracy in VAF estimation is likely key to the success of this approach, and notably, VAFs measured by the cfDNA NGS assay used in this study show good agreement with digital droplet PCR (29,30).…”
Section: Discussionsupporting
confidence: 77%
“…These results suggest that mutation clonality, as it exists in tumor tissue, can be estimated from properly normalized relative cfDNA VAFs, as has been previously hypothesized (28). High accuracy in VAF estimation is likely key to the success of this approach, and notably, VAFs measured by the cfDNA NGS assay used in this study show good agreement with digital droplet PCR (29,30).…”
Section: Discussionsupporting
confidence: 77%
“…This study has several important limitations. First, resistance to targeted therapies may be heterogeneous (10,51), and a single biopsy may not adequately capture the full scope of resistance in a given patient. However, in general, it is not feasible to obtain biopsies of multiple sites in patients with NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…Studies that report normal epithelial cell expansion have tended to initiate culture from early‐stage primary NSCLC tumors, whereas studies in which cancer cells have been expanded have initiated culture using biopsies or effusions from patients with late‐stage, therapy‐resistant disease7, 8, 9 or from PDX models,24 which may be more aggressive and/or more adaptable to cell culture. This would be consistent with traditional NSCLC cell culture methods and PDX models, where patient models are more readily established from late‐stage, metastatic or therapy‐resistant disease than from early‐stage primary disease.…”
Section: Discussionmentioning
confidence: 99%
“…Protocol differences exist between the aforementioned studies: key studies have used inactivated human dermal fibroblasts7, 8 as feeder layers rather than the mouse embryonic fibroblasts often used in those that see normal cell expansion and it has also been possible to transition tumor cell cultures off feeder layers after 6 months of culture establishment 8. We have previously demonstrated that adult human lung fibroblasts do not support long‐term normal airway epithelial cell expansion in the same way as 3T3‐J2 cells17 so the use of adult and/or human feeder cells might favor tumor cell expansion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation